IMPLEMENTASI PERATURAN DAERAH PROVINSI NOMOR 3TAHUN 2015 TENTANG BANTUAN HUKUM BAGI MASYARAKAT MISKIN - Citra Buana; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Legal aid is a special legal service provided to the poor who require free defense, both outside and inside the court, criminal, civil and administrative, from someone who understands the ins and outs of legal defense, principles and rules law, and human rights.In the Criminal Procedure Code (KHUAP). Legal assistance only regulates the conditions for obtaining legal assistance, does not clearly explain what is meant by legal aid itself as contained in Article 56 paragraph (2) which reads: